Management of asymptomatic hypoglycemia with 40% oral dextrose gel in near term at-risk infants to reduce intensive care need and promote breastfeeding - Fabio Meneghin; Martina Manzalini; Miriam Acunzo; Irene Daniele; Petrina Bastrenta; Francesca Castoldi; Francesco Cavigioli; Gian Vincenzo Zuccotti; Gianluca Lista (BMC, 2021)
Abstract Background Neonatal hypoglycemia is a common disorder especially in at-risk infants and it can be associated with poor long-term neurological outcomes. Several therapeutic interventions are suggested, from the implementation of breastfeeding to the glucose intravenous administration. Oral dextrose gel massaged into the infant's inner cheek is a recent treatment option of asymptomatic hypoglycemia, after which oral feeding is encouraged. This approach seems to reduce the admission of infants to neonatal intensive care unit (NICU) so favouring maternal bonding and breastfeeding success at discharge. Methods In our ward, we prospectively compared a group of near-term neonates, (Gr2, n = 308) at risk for hypoglycemia, treated with an innovative protocol based on the addition of 40% oral dextrose gel (Destrogel, Orsana®,Italy) administered by massaging gums and cheek with historical matching newborns (Gr1, n = 389) treated with a formerly used protocol, as control group. The primary outcome was occurrence of NICU admission and the requirement of intravenous glucose administration; while discharge with full breastfeeding was the secondary outcome. Results In Gr1, 39/389 (10%) infants presented with asymptomatic hypoglycemia, 19/39 were transferred to the NICU, and 14/39 required intravenous glucose treatment. In Gr2, among the 30/308 infants with asymptomatic hypoglycemia managed according to the new protocol, 3/30 were transferred to the NICU and received intravenous glucose infusion. The mean duration of hospitalization respectively was 6.43 (± 6.36) and 3.73 ± 1.53 days (p <  0.001). At discharge, 7.7% of the infants in Gr1 and 30% of the infants in Gr2 were exclusively breastfed (p = 0.02). Considering Gr1 vs Gr2, the number of patients that were transferred to NICU was 19 (48.7%) vs 3 (10%) (p = 0.001) and the number of infants that needed intravenous glucose infusion was 14 (35.9%) vs 3 (10%) (p = 0.01), respectively. Conclusions In our population of near term infants, the introduction of 40% oral dextrose gel to the protocol, helped in the safe management of asymptomatic hypoglycemia and, at the same time, implemented breastfeeding.